The Detection and Characterization of Defects in Metal/Non-metal Sandwich Structures by Thermal NDT, and a Comparison of Areal Heating and Scanned Linear Heating by Optical and Inductive Methods; Journal of Nondestructive Evaluation; Vol. 40, iss. 2 - Chulkov A. O. Arseniy Olegovich; Tuschl C.; Nesteruk D. A. Denis Alekseevich; Oswald-Tranta B.; Vavilov V. P. Vladimir Platonovich; Kuimova M. V. Marina Valerievna (2021, 2021)
Title screen